Taxonomy of Gesneriaceae in China and Vietnam - Wen-Hong Chen (PhytoKeys)
China and Vietnam are important center of biodiversity worldwide. Gesneriaceae is a family with extraordinary species richness in China and Vietnam. Within the family, there are more than 600 accepted species in China. The species number will considerably surpass 700 species in China and Vietnam. Furthermore, the massive karst regions between China and Vietnam will provide mega-diverse ecological niches and imply the numerous potential unknown species needing for new discovery. After a long-term collaboration between China and Vietnam, many new findings have been made and research continues even more intensively now-a-days. The special issue will focus on the taxonomy of Gesneriaceae and research progress in China and Vietnam.